Improving the productivity of 19, 20-epoxy-cytochalasin Q in Xylaria sp. sof11 with culture condition optimization. Issue 5 (3rd July 2016) - Zhang, Yun; Cai, Jin; Huang, Lei; Xu, Zhinan; Yang, Xiuliang; Li, Jiangtao; Zhu, Xiangcheng
ABSTRACT: 19, 20-Epoxy-cytochalasin Q (B5A) is a cytochalasin with a wide range of biological activities, which can be produced by Xylaria sp. sof11, a strain isolated from the seafloor of the northern South China Sea. Since the low titer of B5A has greatly limited its further studies, we have systematically conducted the fermentative optimization for B5A production in this article. The effects of major medium components, including the carbon and organic nitrogen sources, as well as of the concentration of sea salt, were respectively investigated through single-factor experiments. As a result, sucrose and fish meal were determined to be the key factors affecting the production of B5A. Then three important variables, sucrose, fish meal, and filling volume, were screened out by the Plackett–Burman (PB) design. The optimal level of these variables was further confirmed by response surface analysis. The final formulated medium was set as 35.2 g/L sucrose and 18.0 g/L fish meal, with filling volume of 34.6 mL, which could afford 440.3 mg/L production of B5A, approximately 4.4-fold higher than that in the original medium. The significantly improved productivity of B5A will facilitate the subsequent mechanistic and clinical studies of B5A.